BASELINE STUDIES OF THE CLAY MINERALS SOCIETY SPECIAL CLAYS: SPECIFIC SURFACE AREA BY THE BRUNAUER EMMETT TELLER (BET) METHOD - Dogan M.; Dogan A.U.; Yesilyurt F.I.; Alaygut D.; Buckner I.; Wurster D.E. (My University, 2007)
The Clay Minerals Society published a complete characterization scheme for its ‘Source Clays' but not for its ‘Special Clays'. To address this issue, the specific surface areas (SSAs) of the 16 special clays from The Clay Minerals Society were determined using the Brunauer, Emmett and Teller (BET) method of adsorption of an inert gas. Two BET measurements were performed for each of the 16 special clays, and the average BET SSA of each of the special clays was determined. The BET SSA of cookeite is reported for the first time. In the present study, special clays from The Clay Minerals Society are classified under three groups based on their BET special surface area values as Group-I special clays, with BET values of 0.1–10 m2/g, Group-II special clays, with BET values of 10–100 m2/g, and Group-III special clays, with BET values >100 m2/g. Comparisons which proved interesting were the those involving the mixed-layer clays and the synthetic clays. The systematic approach employed in this paper will allow for better comparisons to be made between different clays and will provide a comprehensive database for future applications of such material (e.g. as catalyst carriers, as adsorbents in waste treatments, etc.).
Keywords: BEIDELLITE; BET; COOKEITE; ILLITE; ILLITE-SMECTITE; MONTMORILLONITE; NONTRONITE; RECTORITE; RIPIDOLITE; SPECIAL CLAYS; SPECIFIC SURFACE AREA; SYNTHETIC HECTORITE; LAPONITE